A thousand words tell more than just numbers: Financial crises and historical headlines - Kim Ristolainen; Tomi Roukka; Henri Nyberg (Aboa Centre for Economics (ACE), 2021)
We show that financial crises are preceded by changes in specific types of narrative information contained in newspaper article titles. Our novel international dataset and the resulting empirical evidence are gathered by integrating information from a large panel of economic news articles in global newspapers between the years 1870 and 2016 with conventional macroeconomic and financial indicators. We find that the predictive information of newspaper article titles that signals coming crisis episodes is substantial ver and above the macroeconomic and financial indicators. The new indicators capture common features that have often been discussed as potential causes of specific crises but which have not been incorporated into empirical models.
Keywords: G00; G01; N01; C25; C82; 330; financial crisis; text data; leading indicators; topic model